Nulliparous with low-grade cytology - Jerónimo, José (2016)
This section of the magazine aims to review protocols for management of patients with positive screening or diagnosis of cervical lesions. In recent years there have been published new recommendations, and others are in the process of publication, which may cause some confusion among the medical community. In 2013 the World Health Organization released its new guidelines for the prevention of cervical cancer and it considers three options for primary screening: Pap, visual inspection with acetic acid (VIA), and the test for the detection of the human papillomavirus (HPV).